1000 + pictures for teachers to copy - Wright, Andrew (England Longman, 2009)
1000 + pictures for teachers to copy has become one of the best loved books in the language teaching world ... and beyond.
Contents.
Keywords: Learning; Teaching; vocabulary; English - foreign language; Elementary school